(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Water is an important element of conservation in the history of Rajputana states. Aravali mountain range divides Rajasthan into two parts eastern and western. Western Rajasthan consists of desert and receives low rainfall. In this article we have taken the evidences of Bahis which helps us in understanding the importance of conservation of water. These unpublished Bahis are in the state archives of Bikaner which explains the economic, social and administrative conditions. These Bahis carries records relating with administrative decisions and activities. KagadBahi, Sava Bahi, JakatBahi describes about the conservation of water by the people of Marwar. Jhalras, Kuai, bawaris, talab. Taanka, Nadi, Kosita, Kohat and Canch were the Marwari names given to the Water bodies. These Bahis teaches us how to use water in the contemporary world when potable water is getting beyond the approach of common man.